2021
DOI: 10.1002/jor.25129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varus alignment on the bone‐implant interaction of a cementless tibial baseplate during gait

Abstract: Component alignment in total knee arthroplasty is a determining factor for implant longevity. Mechanical alignment, which provides balanced load transfer, is the most common alignment strategy. However, a retrospective review found that varus alignment, which could lead to unbalanced loading, can happen in up to 18% of tibial baseplates. This may be particularly burdensome for cementless tibial baseplates, which require low bone‐implant micromotion and avoidance of bone overload to obtain bone ingrowth. Our ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…More varus alignments shifted the resultant contact force medially to the joint (Figure 3), increased the moment arm to the location of peak micromotion and resulted in more tray tilting at the anterolateral aspect. These findings were in line with previous studies 18,30 . However, a previous study 18 reported 79% increase in peak micromotion during the GT activity due to a 2° varus alignment, whereas the increment was approximately 13% with a similar perturbation in this study.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…More varus alignments shifted the resultant contact force medially to the joint (Figure 3), increased the moment arm to the location of peak micromotion and resulted in more tray tilting at the anterolateral aspect. These findings were in line with previous studies 18,30 . However, a previous study 18 reported 79% increase in peak micromotion during the GT activity due to a 2° varus alignment, whereas the increment was approximately 13% with a similar perturbation in this study.…”
Section: Discussionsupporting
confidence: 94%
“…These findings were in line with previous studies 18,30 . However, a previous study 18 reported 79% increase in peak micromotion during the GT activity due to a 2° varus alignment, whereas the increment was approximately 13% with a similar perturbation in this study. The difference was thought to be because this study considered deformable polyethylene, and femoral‐insert and insert‐tray contact locations off the midline of the tray.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…A negative/positive value meant the bone was under compressive/tensile stress. Bone was considered to be at risk of failure if the compressive or tensile strain exceeded −7300 με or 6500 με [ 41 ]. Von-Mises stress was used to assess the risk of femoral component failure.…”
Section: Methodsmentioning
confidence: 99%